Social support of teammates as a predictor of fear of returning to play among collegiate athletes after injury - Lingan, Ranielle Cloei Calubaquib 2001-; Sabado, Marvin Luis C. (Quezon City College of Human Kinetics, University of the Philippines, 2024)
This study aims to determine if social support from teammates is a significant predictor of the fear of returning to play of collegiate athletes after injury and rehabilitation. It employs a quantitative approach, specifically using the Social Support Questionnaire (SSQ) and Fear to Return Sport Scale (FRESS) as measuring tools to gather data regarding the satisfaction level about social support received and the fear of returning to play of the injured athlete, respectively. The primary goal is to determine if social support from teammates is a significant predictor of the fear of returning to play among collegiate athletes. Participants were selected using a purposive sampling method wherein the criteria must be met. The final scores of the two questionnaires were compared using a linear regression. Other than this, the results were further regressed to see the difference or lack thereof between the using the number of teammates offering support and the satisfaction level on the social support given as a predictor of the fear of returning to play among athletes. The results of this study may be used in the implementation of various communication workshops and training of teams as well as for future research that may delve further into the full impact of social support, considering other factors that are outside the scope of this study such as timing and type of the social support given and the duration and severity of the injury
Thesis (Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Sports injuries; College athletes; Sports teams; Sports -- Psychological aspects